Sustainable Rehabilitation Planning for Coastal Regions Affected by Black Sand Mining - Rahnamarad, Jafar (Journal of Progress in Civil Engineering, 2025)
Alappad, a coastal island situated in Kerala, India is undergoing significant damage and is gradually losing its environmental and social sustainability. The nearby panchayats of Alappad are Clappana and Kulasekharapuram panchayats, which are closely interconnected with Alappad in case of services and the negative impacts on Alappad panchayat will indirectly affect these panchayats also. Here the study area I have taken is Alappad, Clappana and Kulasekharapuram panchayats. I have carried out a socio economic vulnerability assessment of the area through primary surveys and with secondary data collections..This paper is based on formulating strategies for the black sand mining affected area for carrying out a sustainable mining. The study focused on social, environment and economic impacts the black sand mining caused in Alappad.